Assessing COVID-19 knowledge, attitudes, and practices among hospital employees: identifying sociodemographic determinants for improved public health strategies - Aljasim, Layla; Javed, Nargis Begum; Cordoba, Carlos; Alyaseen, Haider; Aljasim, Batool; Aljasim, Mariam; Cordoba, Magdalena; Bugis, Bussma A.; Al-Mohaithef, Mohammed (Frontiers in Public Health, 2024)
Background: Working environment of healthcare institution during pandemic puts all hospital employees at high-risk of being exposed to contagious infections. An individual’s behavior and response are largely determined by their level of knowledge, attitudes and practices (KAP) towards a disease. Therefore, present study aimed to evaluate and assess the KAP towards COVID-19 among hospital employees working in various positions and to identify the sociodemographic determinants associated with level of KAP. Method: A cross-sectional survey was conducted from 1st July to 15th July 2020 in Almoosa Specialist Hospital, Alhasa, in which 221 hospital employees with varied job titles participated. The data for demographics and history of COVID-19 exposure, KAP related to COVID-19 spread and prevention were collected online using a web-based platform (Survey Monkey). Student’s ‘t’ test / One-way ANOVA were used to compare total mean and standard deviation of KAP scores with demographic profile and history of exposure. Results: 89.1% employees knew that COVID-19 virus is mostly transmitted from human-to-human, and 76.0% employees acknowledged droplet transmission. 64.7% employees preferred to take sick person with unconfirmed COVID-19 to health facility. Physicians had higher knowledge scores for COVID-19 infection and non-medical employees had lowest scores (7.47 ± 1.23 and 6.47 ± 1.44, respectively). Nurses had highest practice scores and non-medical employees lowest practice score (6.16 ± 0.74 and 5.37 ± 1.14, respectively). Attitude scores were similar among all the employees. All employees reported increase in hand-washing frequency and avoiding physical contact. Conclusion: The study results revealed socio-demographic factors; level of education, nationality, and field of service are associated with COVID-19 KAP. The study highlights that there is a gap in the level of knowledge about COVID-19, especially among nonmedical employees. A targeted interventional programs need to be planned and implemented to improve COVID-19 awareness among non-medical employees.